2021
DOI: 10.1039/d1qo00175b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient oxidative cleavage of olefins with O2 under catalyst-, initiator- and additive-free conditions

Abstract: Described are the first example of 1,4-dioxane-promoted oxidative cleavage of olefins to carbonyls with atmospheric oxygen as the sole oxidant and the maximum conversion was obtained up to 95%. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
14
0
1
Order By: Relevance
“…Molecular oxygen (O 2 ) as a sustainable, non-toxic, and cheap oxidant has demonstrated plenty of merits compared with other oxidants toward environmentally benign chemistry . In particular, the photoinduced aerobic oxidations recently have received considerable attention since they represent a simple and sustainable strategy for organic synthesis. For example, Wang et al reported a visible-light-induced aerobic oxidation reaction of alkenes for the synthesis of aldehydes and ketones . Recently, He et al disclosed a practical and eco-friendly photocatalytic approach for the switchable synthesis of sulfoxides and sulfones under transition-metal, additive-free, and minimal solvent conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular oxygen (O 2 ) as a sustainable, non-toxic, and cheap oxidant has demonstrated plenty of merits compared with other oxidants toward environmentally benign chemistry . In particular, the photoinduced aerobic oxidations recently have received considerable attention since they represent a simple and sustainable strategy for organic synthesis. For example, Wang et al reported a visible-light-induced aerobic oxidation reaction of alkenes for the synthesis of aldehydes and ketones . Recently, He et al disclosed a practical and eco-friendly photocatalytic approach for the switchable synthesis of sulfoxides and sulfones under transition-metal, additive-free, and minimal solvent conditions .…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, there are no reports on the synthesis of carboxylic acids from alkenes using O 2 as the sole oxidizing agent without an external initiator, catalyst, and additive. In continuation of our on-going research on selective oxidation with O 2 and green synthesis methods, we herein reveal a green and efficient one-pot synthesis of aromatic carboxylic acids via 1,2-dibutoxyethane-promoted oxidative cleavage of olefins with molecular oxygen (Scheme d).…”
Section: Introductionmentioning
confidence: 91%
“…However, there is no literature on preparation methods of aromatic acid from aromatic alcohols using O 2 as the sole oxidant under external catalyst-, additive-, and base-free conditions. As the continuation of our interest in selective oxidation utilizing O 2 as the oxidant and environmentally friendly synthesis protocol [ 29 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], we report an efficient and practical photocatalytic system for the oxygenation of aromatic alcohols to the target acids or ketones without external additives ( Scheme 1 d). Compared with previously reported systems, the protocol was performed successfully with excellent yields at mild reaction conditions, which exhibit a simple post-treatment and could also be applied on one-pot sequential transformation.…”
Section: Introductionmentioning
confidence: 99%